Understanding subject teachers' language-related pedagogical practices in content and language integrated learning classrooms - Hu, Jingjing; Gao, Xuesong (Andy) (Language awareness, 2021)
Research on Content and Language Integrated Learning (CLIL) programmes has yielded mixed results regarding their impact on students' language learning, drawing attention to the role of CLIL teachers. This study draws on teacher language awareness research to explore secondary subject content teachers' language-related pedagogical practices when teaching subject content in the medium of English in Hong Kong, with a focus on their form-focussed processing and facilitation of language learning strategies. In the study, data collected through classroom observation and interviews were analysed. The analysis revealed that the participants covered limited language forms and language learning strategies in teaching. Their (lack of) language-related pedagogical practices were further interpreted with reference to their awareness of the roles of language in teaching, their understanding of the demands of the language used for learning, and their knowledge of EFL/ESL pedagogy. These findings confirm the significance of developing subject teachers' language awareness through CLIL teacher education programmes in successfully implementing CLIL programmes.